Critical Thinking Skills in Biology Learning: A Gender-Based Comparative Study among High School Students in Indonesia - Sepita Ferazona; Nurkhairo Hidayati; Suryanti Suryanti; Linda Linda; Amelia Swastika; Nilofar Mulla; Muh. Azhar Kholidi (AMPLITUDO : Journal of Science and Technology Innovation, 2026)
Critical thinking skills are essential competencies in 21st-century biology learning because they enable students to analyze, evaluate, and interpret scientific evidence. This study aimed to analyze students’ critical thinking skills in biology learning based on gender and school differences. Quantitative comparative design was employed using a critical thinking skills test covering the indicators of interpretation, analysis, inference, evaluation, and explanation. The data were analyzed using descriptive statistics and a two-way ANOVA to examine the effects of gender, school, and their interaction. The results showed that students’ critical thinking skills were generally in the moderate category, with lower achievement in the inference and evaluation indicators, indicating that students still experienced difficulties in drawing evidence-based conclusions and critically evaluating biological information. The two-way ANOVA results revealed that both gender (F = 28.54, p < 0.001, Partial η² = 0.06) and school (F = 4.21, p = 0.02, Partial η² = 0.02) had significant effects on students’ critical thinking skills, whereas the interaction between gender and school was not significant (p = 0.69). Gender showed a stronger influence than school, as indicated by its higher F-value and larger effect size. These findings indicate that both individual characteristics and learning environments contribute to students’ critical thinking skills, although gender accounted for a greater proportion of the explained variance. Therefore, biology instruction should incorporate active and contextual learning strategies that accommodate learner diversity while fostering higher-order thinking and scientific reasoning